2018
DOI: 10.1111/jog.13830
|View full text |Cite
|
Sign up to set email alerts
|

Transabdominal selective feticide in dichorionic twins: Ten years’ experience at a single center

Abstract: Aim: The present study investigates the procedure-related fetal loss rate and obstetrical outcomes of selective feticide in dichorionic twins. Methods: We retrospectively analyzed the data of 44 cases of dichorionic twins. Two different indications for selective feticide were set: (i) the presence of genetic or congenital anomaly; and (ii) an obstetrical indication specified as a past maternal history of preterm delivery that caused fetal death or cerebral palsy of the child. Primarily, data on procedure-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 33 publications
1
11
1
Order By: Relevance
“…In studies of the effect of 2-to-1 reduction on fetal loss, some reported a direct association with timing of the procedure (trend level or significant difference) 17,18,22,23 whereas others found late reduction to be equally safe. [19][20][21]25 Although factors other than indication and timing may affect maternal and fetal outcome in this setting, such as previous PTB, short cervical length, previous conization, and maternal Müllerian anomalies, we were unable to perform a stratified statistical analysis owing to the small sample size of most of the individual studies and the sparsity of the relevant reported data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies of the effect of 2-to-1 reduction on fetal loss, some reported a direct association with timing of the procedure (trend level or significant difference) 17,18,22,23 whereas others found late reduction to be equally safe. [19][20][21]25 Although factors other than indication and timing may affect maternal and fetal outcome in this setting, such as previous PTB, short cervical length, previous conization, and maternal Müllerian anomalies, we were unable to perform a stratified statistical analysis owing to the small sample size of most of the individual studies and the sparsity of the relevant reported data.…”
Section: Discussionmentioning
confidence: 99%
“…Several other trials that did not meet our inclusion criteria supported a possible association between early versus late reduction and rate of PTB, 18,25 whereas others did not. 17,[19][20][21] Recently, Zemet et al 25 compared 172 early elective reductions (11-14 weeks of pregnancy)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greenberg demonstrated that pregnancy was prolonged for women who underwent reduction in the first trimester (37.3 weeks) compared with the second trimester (36.4 weeks) and third trimester (35.3 weeks) [ 23 ]. One study also found that the birth weight of the foetus was significantly increased when SR was performed at a time point that was earlier than 15 weeks [ 24 ]. Bigelow et al suggested that foetal loss and preterm delivery after SR for twin pregnancies was associated with increasing gestational age at the time of the procedure [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of data on feticide from 44 cases involving dichorionic (DC) twins was undertaken by Kim et al (2019) in South Korea. Two study groups were fairly evenly divided between two indications for feticide given above (Group I: Anomaly, and Group II: Birth History).…”
Section: Selective Feticide In Dichorionic Twinsmentioning
confidence: 99%